DNA Dissipative System for Controlled Release of Immunostimulatory CpG Oligodeoxynucleotides - Aman Ishaqat; Xiaofeng Zhang; Andreas Herrmann (Advanced NanoBiomed Research)
Herein, a dissipative system tailored for the controlled loading and release of CpG oligodeoxynucleotides (CpG ODNs), known for their pharmacological immunostimulatory properties, is reported. The approach involves multiple cycles of deactivation and activation of the CpG ODNs via its hybridization with a complementary fuel strand, followed by its selective release mediated by the enzymatic activity of T7 exonuclease. The autonomous and temporal behavior of this dissipative system can be tuned by three factors: the design of the fuel strand and its concentration that governs the kinetics of the forward hybridization reaction, as well as the concentration of T7 exonuclease, which regulates the backward energy dissipation reaction. Furthermore, the enzyme's tolerance toward waste accumulation is demonstrated, and the system's robust performance when utilizing various fuel strands in alternating fashion is showcased. The findings underscore the potential of this approach for precise and programmable delivery of therapeutic nucleic acids in multiple cycles, with implications for enhancing immunotherapeutic strategies in which controlled kinetics of the nucleic acid is highly desired.